2013
DOI: 10.1021/ef401072s
|View full text |Cite
|
Sign up to set email alerts
|

Improved Experimental Determinations of Phase Equilibria and Structural Transitions of Mixed Gas Hydrates under Isothermal Conditions

Abstract: Investigations on the intrinsic properties of gas hydrates with multiple guests are essential to scientific and technological fields. In particular, even though evaluating and designing a hydrate phase process require isothermal phase equilibria, it is difficult to obtain extensive data with various components and compositions in a short period of time due to the static-analytic method. The present study introduces a new experimental determination on hydrate phase equilibria using continuous dissociation induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…11 In that report, we demonstrated that our newly developed method enables an approximate determination of structural transition points with an accuracy comparable to Raman spectroscopy. In addition, the lower transition point of incipient CH 4 + C 2 H 6 hydrates at 283.10 K was determined in advance of the present work.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…11 In that report, we demonstrated that our newly developed method enables an approximate determination of structural transition points with an accuracy comparable to Raman spectroscopy. In addition, the lower transition point of incipient CH 4 + C 2 H 6 hydrates at 283.10 K was determined in advance of the present work.…”
Section: Resultsmentioning
confidence: 84%
“…31 Table 3 lists all the results of isothermal phase equilibrium measurements in our previous and present studies. 11 These transition points can be ascribed to the change in structural behavior from sII inhibition to sII promotion by connecting the coordinates. However, a more detailed analysis of structural transitions needs to be carried out to ensure the accuracy of the experimental data and fitting results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations